Who are the high achievers at work? Perceived motivational climate, goal orientation profiles, and work performance. Issue 6 (28th September 2018) - Nerstad, Christina G. L.; Richardsen, Astrid M.; Roberts, Glyn C.
Abstract : The purpose of this study was to respond to the call for research on goal orientation (mastery and performance orientation) profiles in work contexts. Among 8, 282 engineers and technologists, Latent profile analyses indicated that four different goal orientation profiles existed – primarily mastery oriented, indifferent, moderate multiple goals, and success oriented. Both success oriented employees and employees who are primarily mastery oriented indicated the highest individual work performance. Further, mastery and performance climates were found to be relevant antecedents of employees' goal orientation profiles. Supplementary analyses suggested that a primarily mastery oriented profile seems to be more beneficial for the facilitation of employee well‐being. The practical implications of these findings and directions for future research are presented.